Regulation of FA and TAG biosynthesis pathway genes in endosperms and embryos of high and low oil content genotypes of Jatropha curcas L - Sood, Archit (Plant physiology and biochemistry : PPB, 2015)
Copyright © 2015 Elsevier Masson SAS. All rights reserved.